The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/epi.16686
|View full text |Cite
|
Sign up to set email alerts
|

Seizure‐onset regions demonstrate high inward directed connectivity during resting‐state: An SEEG study in focal epilepsy

Abstract: Objective: In patients with medically refractory focal epilepsy, stereotactic-electroencephalography (SEEG) can aid in localizing epileptogenic regions for surgical treatment. SEEG, however, requires long hospitalizations to record seizures, and ictal interpretation can be incomplete or inaccurate. Our recent work showed that non-directed resting-state analyses may identify brain regions as epileptogenic or uninvolved. Our present objective is to map epileptogenic networks in greater detail and more accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 46 publications
5
53
0
Order By: Relevance
“…The source-sink hypothesis is supported by clinical evidence based on the levels of glutamate and glutamate receptors in the brain [55][56][57][58] and iEEG studies that have demonstrated strong inward (inhibitory) connectivity to the EZ regions during rest. 59,60,63,64 We evaluated the predictive value of the SSI by a) rating the correspondence between the hypothesized CA-EZ and regions with high SSIs and b) building a random forest to model the probability of a successful surgery as a function of the source-sink metrics, and compared the performance to that of HFOs, a commonly used interictal iEEG feature. The analysis was performed on data from 65 patients treated across 6 clinical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source-sink hypothesis is supported by clinical evidence based on the levels of glutamate and glutamate receptors in the brain [55][56][57][58] and iEEG studies that have demonstrated strong inward (inhibitory) connectivity to the EZ regions during rest. 59,60,63,64 We evaluated the predictive value of the SSI by a) rating the correspondence between the hypothesized CA-EZ and regions with high SSIs and b) building a random forest to model the probability of a successful surgery as a function of the source-sink metrics, and compared the performance to that of HFOs, a commonly used interictal iEEG feature. The analysis was performed on data from 65 patients treated across 6 clinical centers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a high inward directed influence to the EZ at rest. 55,[67][68][69] In a recent study Narasimhan et al 67 stated that high inward connectivity may reflect inhibitory input from other regions to prevent the onset and spread of seizure activity, but the direction of these signals may flip when seizure activity begins. This is supported by iEEG studies in neocortical epilepsy demonstrating functional isolation of epileptogenic areas at rest 70,71 and that increased synchronization in seizure-onset regions may be suggestive of an inhibitory surround.…”
Section: Biological Evidence Supporting the Source-sink Hypothesismentioning
confidence: 99%
“…The golden standard of localization of epileptogenic brain regions in clinical practice typically depends on capturing multiple seizures during the intracranial monitoring process, that may take multiple days or even weeks to complete (14). As such, a method which can estimate SOZ and predict prognosis outcome from analysis of brief, resting-state data segments would have tremendous clinical values to identify epileptogenic networks without requiring prolonged intracranial recordings, which would vastly improve patient care and reduce medical cost (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The underpinnings of seizure generation involve abnormal brain structures and aberrant functional connections among these regions, leading to large-scale network instability ( 30, 31 ). Resting-state network connectivity studies have suggested predominantly increased functional connectivity involving the EZ and surrounding structures ( 15 ), and stronger inward directional connectivity toward EZ ( 16 ). Furthermore, decreased interictal network synchrony and local heterogeneity was found to correlate with improved seizure outcome ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the correct localization of the EZ to achieve seizure freedom after surgery, is still an unsolved and open question, as indicated by the high rate of failure of seizure control (30-40%) after surgery (Spencer and Huh, 2008;Bulacio et al, 2012). The advanced signal processing approaches, especially those based on the connectivity analysis, have been largely applied to stereoelectroencephalography (SEEG) from the patients with epilepsy to better pinpoint the location of the EZ (Varotto et al, 2013;Bartolomei et al, 2017;Adkinson et al, 2019;Narasimhan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%